In Vitro Mass Propagation of Withania Somnifera (L.) Dunal An Important Medicinal Plant of Bangladesh (Bangladesh Journal of Botany, 2022)
An efficient in vitro regeneration system was developed for Withania somnifera (L.) Dunal through direct and indirect organogenesis from nodal and leaf segment explants. Highest direct shoot regeneration was recorded when nodal explants were cultured on MS with 2.0 mg/l BAP and 0.5 mg/l NAA where the average number of shoots per explants was 10.5. For indirect regeneration remarkable results on shoot initiation were observed when node and leaf segment callus were cultured on MS +1.0 mg/l BAP +0.5 mg/l NAA. It was observed that node callus showed best response for multiple shoot/explants (28.9) on MS +1.0 mg/l BAP +0.5 mg/l NAA. But the mean of shoots from the callus of leaf segment explants was found to be 15.1 on the same media. The best response towards root induction was observed on MS with 2.5 mg/l IBA. The well rooted plants were successfully acclimatized and transferred to soil.Bangladesh J. Bot. 51(2): 191-197, 2022 (June)